1996
DOI: 10.1046/j.1464-410x.1996.11012.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term predictive role of urodynamics: an 8‐year follow‐up of prostatic surgery for lower urinary tract symptoms

Abstract: Uroflowmetry and pressure-flow studies can predict to some degree the long-term result after prostatic surgery. There was a durable effect on symptom scores and maximum flow rates after the operation. The annual rate of repeat resection (1.8%) was relatively low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…6 Eight years after undergoing TURP, 12.0% to 15.5% of patients need re-intervention. 7 Minimally invasive treatments, such as PVP, TUNA and transurethral microwave treatment (TUMT), have reoperation rates of 11%, 8%, and 7%, respectively, after 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…6 Eight years after undergoing TURP, 12.0% to 15.5% of patients need re-intervention. 7 Minimally invasive treatments, such as PVP, TUNA and transurethral microwave treatment (TUMT), have reoperation rates of 11%, 8%, and 7%, respectively, after 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown repeatedly that patients with urodynamically confirmed obstruction profit more from prostatectomy than do those without [12,18,[20][21][22][23]. Ball et al studied the long-term outcome 5 years after prostatectomy in 83 patients and correlated post-operative results with the pre-operative urodynamics [20].…”
Section: Discussionmentioning
confidence: 99%
“…reported by others and by a recent update from Jensen et al [18,23]. Consequently, it has been speculated that Pressure flow studies have shown that 20-30% of all patients undergoing prostatectomy are urodynamically the consistent post-prostatectomy failure rate of about 20% in most published series is caused by the inclusion not obstructed [10,12,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In Roos’ et al [3]multicenter study of 39,077 patients undergoing TURP in Denmark (n = 27,911), England (n = 2,171) and Canada (n = 8,995), the rate of reintervention after TURP increased from 2.34.3% within 12 months to 8.9–9.7 and 12.0–15.5% 5 and 8 years after surgery, respectively. Jensen et al [4]calculated a repeat resection rate of 1.8% per year after TURP. In a contemporary large–scale monocenter study, 0.9 and 2.5% of patients had to undergo repeat resection within 12 and 36 months after initial TURP [5].…”
Section: Introductionmentioning
confidence: 99%